Estimation of the in-cylinder residual mass fraction at intake valve closing in a two-stroke high-speed direct-injection compression-ignition engine. (June 2020) - Torregrosa, Antonio; Martín, Jaime; Novella, Ricardo; Thein, Kevin
New combustion concepts and engine designs are being currently investigated in order to comply with upcoming pollutant regulations and reduce fuel consumption. In this context, two-stroke architectures appear as a promising solution for the implementation of some combustion concepts. However, scavenging processes in a two-stroke engine are much more challenging than for a four-stroke engine, and the residual mass of burnt gases retained inside the cylinder needs to be properly determined in order to keep control over the in-cylinder composition, hence over the combustion conditions and pollutant emissions. In this study, a new methodology for the estimation of the internal residual gas fraction is introduced, which is based on the thermodynamic processes occurring in the engine investigated and makes use of basic engine instrumentation and measurement equipment usually available in a conventional test cell. Several versions of the estimator were developed so that different requirements could be met, such as those of real-time estimation on an engine test bench but with reduced precision or, on the contrary, highly precise but time-consuming computations for post-processing purposes and combustion diagnosis. The consistency of the internal residual gas estimator was then validated through its application to real engine tests at different operating points.